1999
DOI: 10.1074/jbc.274.50.35985
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the Extracellular Domain of the Receptor for Epidermal Growth Factor Containing the Membrane-spanning Segment in Response to Treatment with Epidermal Growth Factor

Abstract: A recombinant fragment of the human receptor for epidermal growth factor containing both its extracellular domain and its membrane-spanning segment, when dissolved with Triton X-100, was observed to dimerize in response to addition of epidermal growth factor (EGF) even at the lowest concentration of this fragment that could be assayed (4 nM). Consequently, the dissociation constant for the dimer of this fragment is at least 10,000-fold smaller than that for dimers of soluble, recombinant forms of the extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 27 publications
(48 reference statements)
6
62
1
Order By: Relevance
“…The view that EGFR extracellular domains in the absence of ligands inhibit dimerization was first proposed by Tanner and Kyte, who carried out dimerization studies of the extracellular domain (50). Tanner and Kyte argued that the role of the ligand is to eliminate the steric repulsion between the extracellular domains.…”
Section: Structural Determinants Of Rtk Activation Extracellular Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The view that EGFR extracellular domains in the absence of ligands inhibit dimerization was first proposed by Tanner and Kyte, who carried out dimerization studies of the extracellular domain (50). Tanner and Kyte argued that the role of the ligand is to eliminate the steric repulsion between the extracellular domains.…”
Section: Structural Determinants Of Rtk Activation Extracellular Domainsmentioning
confidence: 99%
“…In one study, aimed at elucidating the relative contributions of the extracellular domain and the TM domain, Tanner and Kyte showed that the extracellular EGFR domains dimerize strongly only in the presence of the TM domains (50). The dissociation constant of the extracellular domains, when attached to the TM domains, was estimated to be least 10,000 fold smaller, as compared to the dissociation constant of the isolated extracellular domains.…”
Section: Tm Domainsmentioning
confidence: 99%
“…The neu oncogene encodes a Val 3 Glu substitution in the TM domain of ErbB2 that results in constitutive activation (34). Recombinant EGFR fragments consisting of the extracellular and TM domains have a 10 5 -fold higher affinity for dimerization than the isolated soluble extracellular domains (31). The TM domains of all four ErbB family members self-associate when expressed in bacterial inner membranes (26).…”
mentioning
confidence: 99%
“…Further studies have also provided evidence that specific interactions between the TM helices of ErbB2 can mediate dimerization and receptor activation (8). In contrast to these findings, Tanner and coworkers have argued that interactions between the TM domains do not contribute significantly to ErbB2 receptor dimerization (9). Thus, the structural picture of the TM domain of ErbB2 remains elusive despite the extensive research devoted to this important protein.…”
Section: Introductionmentioning
confidence: 82%